2019
DOI: 10.1111/jzs.12326
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the European free‐tailed bat, a tropical affinity species spanning across the Mediterranean Basin

Abstract: The Mediterranean Basin is a global biodiversity hotspot, hosting a number of native species belonging to families that are found almost exclusively in tropical climates.Yet, whether or not these taxa were able to survive in the Mediterranean region during the Quaternary climatic oscillations remains unknown. Focusing on the European free-tailed bat (Tadarida teniotis), we aimed to (a) identify potential ancient populations and glacial refugia; (b) determine the post-glacial colonization routes across the Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Alternatively, physical barriers, such as mountains and rivers, were previously reported to have played important roles in bat adaptive evolution (Flanders, Wei, Rossiter, & Zhang, 2011; Kuo, Chen, Fang, Flanders, & Rossiter, 2014). However, other studies found that physical barriers may not influence bat diversification owing to their high dispersal ability (Amorim et al., 2019; Goodman, Maminirina, Bradman, Christidis, & Appleton, 2010; Liu, Sun, Park, & Feng, 2016; Weyeneth, Goodman, & Ruedi, 2011). In this study, a generally high level of nuclear gene flow was observed (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, physical barriers, such as mountains and rivers, were previously reported to have played important roles in bat adaptive evolution (Flanders, Wei, Rossiter, & Zhang, 2011; Kuo, Chen, Fang, Flanders, & Rossiter, 2014). However, other studies found that physical barriers may not influence bat diversification owing to their high dispersal ability (Amorim et al., 2019; Goodman, Maminirina, Bradman, Christidis, & Appleton, 2010; Liu, Sun, Park, & Feng, 2016; Weyeneth, Goodman, & Ruedi, 2011). In this study, a generally high level of nuclear gene flow was observed (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting findings may be caused by sex‐biased dispersal in bats (Amorim et al., 2019; Centeno‐Cuadros et al., 2019; Demos et al., 2019; Fornůsková et al., 2014; Moussy et al., 2013; Yoshino et al., 2008). Under the pattern that involves male dispersal but female philopatry, nuclear differentiation covaried with geographic distance over a large scale (Figure c) because of the long‐distance movements of male bats and caused a spatial pattern of IBD (Moussy et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This approach assumes that genetic relatedness that differs from the expected, provides a proxy for the disruption of social structure at breeding colonies through the arrival of new individuals (Wilkinson et al, 2019). To calculate genetic relatedness, we genotyped 1,407 individuals at 14 polymorphic microsatellites, following the procedures in Amorim, Razgour, et al (2020) and described in Appendix D. Relatedness analyses were done using CoanCestRy software (Wang, 2011) and Related R package (Pew et al, 2015), assuming Wang's estimator (Appendix D). To test for significant differences in genetic relatedness, we first computed the observed average relatedness difference between each 'period' (before, during and after) at each 'location' (near vs. far).…”
Section: Genetic Relatednessmentioning
confidence: 99%
“…This study tests expectations regarding the consequences of population crowding, defined here as a transient influx of individuals to refuges after habitat loss. We focus on a new hydroelectric reservoir (Baixo Sabor; NE Portugal) and the European free‐tailed bat Tadarida teniotis , a medium‐sized, crevice‐dwelling insectivorous bat, with a core distribution in the Mediterranean region (Amorim, Razgour, et al., 2020). The European free‐tailed bat provided a convenient model to test population‐level consequences of crowding, because it roosts in rocky crevices along the river valley flooded by the hydroelectric dam, but also in bridges not affected by flooding (Amorim et al., 2015; LEA, 2014).…”
Section: Introductionmentioning
confidence: 99%